2014
DOI: 10.3109/09637486.2014.953450
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic effects ofLactobacillus reuteriLR6 in rats fed on high-cholesterol diet

Abstract: The bacterium Lactobacillus reuteri LR6, an isolate from breast-fed human infant feces, was tested positive for bile tolerance and bile salt hydrolase activity. It was also evaluated as a potential probiotic with cholesterol-lowering effect in vivo. In this study, 32 male Albino rats were divided into four groups consisting of eight mice per group. For 60 d, group I was fed with normal synthetic diet, group II was fed with cholesterol-enriched diet only, group III was fed with cholesterol-enriched diet supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…In fact, the effects of probiotic strains on hypercholesterolemia has been observed in many studies. 4, 6, 20, 21 Yet, there is no doubt that vast of further researches are needed and there is still a long way to go.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the effects of probiotic strains on hypercholesterolemia has been observed in many studies. 4, 6, 20, 21 Yet, there is no doubt that vast of further researches are needed and there is still a long way to go.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of administration of ATO and strains were determined by referring to previous studies and was verified by preliminary experiments. 6,15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of cholesterol removal of L. lactis WH-C1 in vitro Several researches on the potential hypocholesterolemic properties of bacterial strains have been carried out (15,16). Strains belonging to different species and genera have been investigated their cholesterol removal action in vitro (17,18) and in vivo (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, probiotics have been paid close attention and are considered as dietary adjuncts in novel probiotic foods. It has been reported that lactic acid bacteria such as in Lactobacillus acidophilus (Park et al ., ), Lactobacillus plantarum (Kumar et al ., ; Salaj et al ., ), Lactobacillus paracasei (Chiu et al ., ), Lactobacillus reuteri (Singh et al ., ), Enterococcus faecium (Cavallini et al ., ), Lactobacillus fermentum (Xie et al ., ) and Bifidobacterium longum (Al‐Sheraji et al ., ) had the ability to lower serum cholesterol (Table ). In this study, Lactobacillus plantarum DMDL 9010 which was isolated from Chinese fermented Mustard showed the ability to lower the cholesterol content in vitro (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 99%